Desain Kemasan Buah Rambutan (Nephelium lappaceum L.) untuk Distribusi dan Pemasaran dalam Satuan Eceran (Ritel) - Andi Marlisa Bossa Samang; Emmy Darmawati; Lilik Pujantoro Eko Nugroho (Jurnal Keteknikan Pertanian, 2018)
AbstractRambutan is a top fruit from Indonesia, but it has not been get a good postharvest handling. One of the less postharvest handling is using of distribution packaging or retail marketing on fruit stores. The purpose of this research were designing a retail packaging made from polypropylene (PP) film and distribution packaging made from corrugated board. The stages of this research were to determine weight per unitpackaging of rambutan (retail and distribution), dimension of primary and secondary packaging, and analyze the efficiency of packaging arrangement on pallet. Rambutan cv. Lebak was picked from Subang, West Java Province with grade A fruit. The weight average of rambutan was 34.53 ± 2.32 g with individual volume was 21.29 cm3. The weight per retail packaging was 0.5 kg and each distribution packaging contain 4 packaging retail of rambutan. Based on the data, dimension of primary packaging was 12.5 x 12.5 x 15 cm that formed pouch bag with perforated (30 holes). Position of holes were placed with two options on the packaging surface. The RSC type secondary packaging was 28.5 x 28.5 x 16.5 cm for square packaging and the size 33.5 c 20.5 x 16.5 cm for rectangle packaging made from BC flute kraft 150 g. The simulation result shows efficiency of packaging arrangement above pallet should use size 1200 x 1000 mm (effieciency 81.22%) for square packaging and on pallet size 1067 x 1067 mm (effieciency 90.50%) for rectangle packaging.AbstrakRambutan merupakan buah unggulan Indonesia, namun belum mendapat penanganan pascapanen yang memadai. Salah satu penanganan yang masih minim adalah penggunaan kemasan dalam distribusi maupun penjualan di toko buah dalam bentuk eceran (ritel). Tujuan penelitian adalah merancang kemasan ritel berbahan plastik polypropylene (PP) dan kemasan distribusi berbahan karton gelombang. Tahapanpenelitian adalah penentuan satuan berat per kemasan (eceran dan distribusi), dimensi kemasan primer dan sekunder serta efisiensi penyusunan kemasan pada pallet untuk handling. Buah rambutan yang digunakan adalah varietas Lebak mutu A dari Kabupaten Subang, Jawa Barat dengan berat rata-rata 34.53 ± 2.32 g dan volume 21.29 ± 2.45 cm3. Berat per kemasan eceran dibuat 0.5 kg dan tiap kemasan distribusi berisi 4 buah kemasan eceran. Berdasarkan data tersebut, diperoleh dimensi kemasan primer 12.5 x 12.5 x 15 cm dibentuk pouch dengan jumlah perforasi 30 lubang yang diletakkan dengan dua pilihan posisi dipermukaan kemasan. Kemasan sekunder tipe RSC berukuran 28.5 x 28.5 x 16.5 cm untuk bentuk kotak dan 33.5 x 20.5 x 16.5 cm untuk bentuk persegi dengan bahan flute BC dari kertas kraft 150. Hasil simulasi penyusunan kemasan diatas palet menunjukkan, untuk bentuk kotak sebaiknya menggunakan palet ukuran 1200 x 1000 mm (efisiensi 81.22%), bentuk persegi menggunakan palet ukuran 1067 x 1067mm (efisiensi 90.50%).